Quantitative research course - Hasmadi, Hassan; Hafizoah, Kassim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
6 September 2012. A one-day course on quantitative research for social scientist was conducted at CENFED Training Room. The course was organized based on the initiatives of the Human Sciences (HS Department) lecturers to keep align with the advancement of current research activities.